Analyzing the Determinants of the Matching of Public School Teachers to Jobs: Disentangling the Preferences of Teachers and Employers - Boyd, Donald; Lankford, Hamilton; Loeb, Susanna; Wyckoff, James (Journal of Labor Economics, 2013)
This article uses a game-theoretic, two-sided matching model and method of simulated moments estimation to study factors affecting the match of elementary teachers to their first jobs. We find that employers demonstrate preferences for teachers having stronger academic achievement (e.g., attended a more selective college) and for teachers living in closer proximity to the school. Teachers show preferences for schools that are closer geographically, are suburban, have a smaller proportion of students in poverty, and, for white teachers, have a smaller proportion of minority students. These results appear predictable but contradict findings from prior research estimating hedonic wage equations for teacher labor markets.